CULTURAL CONNOTATIVE CHARACTERISTICS OF REALIAS (Scientific journal of the Fergana State University, 2024)
Translation is the most important tool of modern integrative intercultural communication. Translation is a connection that strengthens the relationship between two languages as well as cultures. In this process, issues such as the relationship between language and culture, as well as a wide range of national-cultural units reflected in them, the processes of their formation and areas of application, their manifestation at the level of language, manifestation in speech and writing, have been carefully studied. The purpose of the study is to determine the national-cultural, lexical-semantic, stylistic characteristics of realias in English literary context, as well as to highlight issues of their translation into the Uzbek language.